2022
DOI: 10.1094/pdis-09-21-1877-re
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Infection Biology of Teratosphaeria destructans and Teratosphaeria epicoccoides on Eucalyptus

Abstract: Leaf blight caused by Teratosphaeria destructans is one of the most important diseases of Eucalyptus planted in the sub-tropics and tropics. In contrast, the better-known Teratosphaeria epicoccoides, while also a primary pathogen of Eucalyptus, causes less damage to trees in these areas. Although T. destructans is an aggressive pathogen, nothing is known about its infection biology. In this study, the conditions for infection and disease development caused by T. destructans and T. epicoccoides were evaluated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Both species are widely distributed in Eucalyptus plantations that are mainly distributed across regions of southern China. Although previous studies have indicated that T. epicoccoides and T. destructans are widely distributed on Eucalyptus leaves globally [ 41 , 44 ], research on these species on diseased Eucalyptus leaves specifically in China is limited. During the sampling process in the current study, we found that the severity caused by each species of T. epicoccoides and T. destructans on different genotypes of E. urophylla × E. grandis were different.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both species are widely distributed in Eucalyptus plantations that are mainly distributed across regions of southern China. Although previous studies have indicated that T. epicoccoides and T. destructans are widely distributed on Eucalyptus leaves globally [ 41 , 44 ], research on these species on diseased Eucalyptus leaves specifically in China is limited. During the sampling process in the current study, we found that the severity caused by each species of T. epicoccoides and T. destructans on different genotypes of E. urophylla × E. grandis were different.…”
Section: Discussionmentioning
confidence: 99%
“…At present, on a global scale, methods for assessing the pathogenicity of Mycosphaerellaceae and Teratosphaeriaceae species isolated from diseased Eucalyptus leaves include spraying ascospore suspensions, conidial suspensions, hyphal fragment suspensions, or a mixture of spores and hyphal fragment suspensions onto Eucalyptus seedlings in controlled environments. Additional inoculation methods involve applying ascospore masses or lesions from diseased leaf areas onto Eucalyptus seedling leaves [44,57,64]. Conidial suspensions are considered to be a typical method for evaluating the pathogenicity of Mycosphaerellaceae and Teratosphaeriaceae species; however, this is not possible for species that do not sporulate sufficiently in culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation